Kemunduran Demokrasi di Indonesia dan Gerakan untuk “Back to Nature” Menurut Perspektif Rousseau: The Decline of Democracy in Indonesia and the Movement for “Back to Nature” According to Rousseau's Perspective - Dori, Petrus; Kleden, Fransiskus Bala; Jehalut, Ferdinandus (Jurnal Filsafat Indonesia, 2025)
It should be realized that Indonesian is in a situation of democratic decline. The democracy index in Indonesia continues to decline every year. This decline can be seen from two facts, which are, first, the weakening of civil society criticism in the public sphere, and second, the function of government which tends to deny the legitimacy of opponents because it wants to maintain power. This research aims to examine the relevance of Jean Jacques Rousseau’s “Back to Nature” ideas in the context of democracy in Indonesia. This article used a qualitative-descriptive method with a literature study approach. Based on the research results, it was found that Rousseau’s “Back to Nature” idea was a good guide for the Indonesian citizens in restoring the nation’s democratic spirit. Indonesian democracy must “Back to Nature”. This does not mean that Indonesian citizens have to return to primitive times. “Back to Nature” means returning to the authentic meaning of democracy. This is done by forming a solid pro-democracy alliance or coalition. This alliance movement must be carried out in the political, institutional and social arenas at the same time. Indonesian democracy will return to its original state and popular sovereignty can be re-established if these three elements of this nation can work together to build democracy and repress authoritarianism within the nation’s democratic body.